Intrinsic and acquired resistance to HER2-targeted therapies in HER2 gene-amplified breast cancer: mechanisms and clinical implications - Rexer, Brent N; Arteaga, Carlos L (Critical reviews in oncogenesis, 2012)
Approximately 25% of human breast cancers overexpress the HER2 (ErbB2) proto-oncogene, which confers a more aggressive tumor phenotype and associates with a poor prognosis in patients with this disease. Two approved therapies targeting HER2, the monoclonal antibody trastuzumab and the tyrosine kinase inhibitor lapatinib, are clinically active against this type of breast cancer. However, a significant fraction of patients with HER2+ breast cancer treated with these agents eventually relapse or develop progressive disease. This suggests that tumors acquire or possess intrinsic mechanisms of resistance that allow escape from HER2 inhibition. This review focuses on mechanisms of intrinsic and/or acquired resistance to HER2-targeted therapies that have been identified in preclinical and clinical studies. These mechanisms involve alterations to HER2 itself, coexpression or acquisition of bypass signaling through other receptor or intracellular signaling pathways, defects in mechanisms of cell cycle regulation or apoptosis, and host factors that may modulate drug response. Emerging clinical evidence already suggests that combinations of therapies targeting HER2 as well as these resistance pathways will be effective in overcoming or preventing resistance.